The pedagogical practices of science and mathematics teachers with students with specific educational needs: a case study (Research, Society and Development, 2020)
Inclusive education is  in the legislation and official documents that regulate Brazilian education, it is important to investigate how it happens in schools in different areas of knowledge and in this study we will investigate this aspect in Science and Mathematics Teaching. The target audience of the research was seven teachers from these areas of a State College of Full-time (CEPI), located in Itumbiara-GO. We aim to know how these teachers have worked and conceived when working with students with specific educational needs (SEN) in the last  years of elementary school.  The bibliographic research, reading and analysis of legislation pertinent to the theme and application of a questionnaire comprised data collection and the analysis was carried out according to Bardin's content analysisThe results of this study suggest a specific formation could promote a Science and Mathematics teaching more inclusive and it could help gradually overcoming the difficulties in preparing materials for students with sen, it will be good for teacher know how to evaluate these students and how to identify their needs, potential and learning limits Finally, we consider that, despite having the legislation that claims to guarantee the rights of people sen, this is not enough to become a reality, because in addition to the lack of resources, we have problems in the initial training of teachers. Many universities still is not enough prepared to teach of the professional that needs to work in inclusive education. Thus, we understand the need and the importance of continuing teacher education so that they can develope a diversified educational practice and that considere the potencial of students with sen.